2018
DOI: 10.1111/jgh.14123
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced B‐cell differentiation driven by advanced cirrhosis resulting in hyperglobulinemia

Abstract: Enhanced TLR9-induced differentiation into antibody secreting cell may explain peripheral reductions of circulating CD27 memory B cells as well as increased serum Ig levels in cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…B cells in HBV-related advanced cirrhosis had a lower percentage of memory B cells, a higher ratio of plasmablasts and an increased percentage of naïve B cells, which was in accordance with the findings of other studies ( 10 , 11 ). Memory B cells were chronically activated in advanced cirrhosis, as memory B cells in advanced cirrhosis were more easily activated by TLR9 plus elevated PAMP levels in cirrhotic conditions ( 10 , 11 ). Activated memory B cells differentiate into short-lived antibody-secreting plasmablasts, increasing the percentage of plasmablasts and the consumption of memory B cells ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…B cells in HBV-related advanced cirrhosis had a lower percentage of memory B cells, a higher ratio of plasmablasts and an increased percentage of naïve B cells, which was in accordance with the findings of other studies ( 10 , 11 ). Memory B cells were chronically activated in advanced cirrhosis, as memory B cells in advanced cirrhosis were more easily activated by TLR9 plus elevated PAMP levels in cirrhotic conditions ( 10 , 11 ). Activated memory B cells differentiate into short-lived antibody-secreting plasmablasts, increasing the percentage of plasmablasts and the consumption of memory B cells ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…A decrease in the CD27 + memory subgroup among cirrhotic B cells may contribute to this effect ( 10 ). Regarding B cell functional changes after stimulation, the conclusions were contradictory: one result showed that activation of peripheral B cells in cirrhosis was attenuated after CD40/TLR9 stimulation, manifesting as reductions in CD70 expression and IgG production ( 10 ), and the other result demonstrated that cirrhotic B cells were prone to differentiate into plasma cells and produce increased amounts of immunoglobulins ( 11 ). Although the damaged humoral response in cirrhosis has been confirmed, the mechanism and B cell response after activation, especially the T cell-dependent B cell response, remain to be further explored, as T cell help plays a pivotal role in humoral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of hyperactive Tfh cells to plasma cell differentiation may lead to the increased levels of non-specific antibodies and autoimmune antibodies during cirrhosis. It is reported that cirrhotic patients manifested hyper-immunoglobnemia (9) and had more anti-microbial antibodies than control subjects (27). Therefore, the enhanced systemic inflammation and Tfh cell immunity in cirrhotic patients may break the barrier tolerance and facilitate the induction of anti-microbial antibodies, which consequently affect the normal symbiosis of gut flora and lead to the increased microbial translocation.…”
Section: Discussionmentioning
confidence: 99%
“…LC profoundly depletes the circulating CD27 + memory B cells (7, 8). Accompanying this, hyper-globulinemia and elevated IgG and IgA levels were observed in advancing cirrhosis, irrespective of the underlying etiology (9). LC also causes T cell lymphopenia and disrupts T cell compartments.…”
Section: Introductionmentioning
confidence: 94%
“…Globulins consist of several proinflammatory proteins (14), including C-reactive protein, α2-macroglobulin, fibrinogen, prothrombin, and serum amyloid A (34). Since immunoglobulins in humans are mainly metabolized by the liver, the ability to clear immunoglobulins in patients with severe hepatic dysfunction may be reduced, resulting in hyperglobulinemia (35,36).Tumor-related inflammation stimulates the production of various cytokines, such as interleukin (IL)-1, IL-6, and tumor necrosis factor (37), which can act on the liver and induce the synthesis of positive acute-phase reactants (34). This might explain the increased serum globulin levels observed in this study.…”
Section: Discussionmentioning
confidence: 99%